Locative Inversion In Discourse: a strategy of non-commitment - Christine Copy; Lucie Gournay (Discours)
In this paper, Locative Inversion (hence LI) is analysed as the linear realization of a predication devoid of speaker’s commitment. First, we show that the syntactic constraints and modal restrictions already debated in the linguistic literature, form a coherent set of properties and are evidence of a non-speaker-based predication. Some examples of these properties are: LI’s incompatibility with negation or epistemic modalization, strong aspectual and temporal restrictions such as its incompatibility with BE+ING or generic interpretations.In the second part of this paper, we provide a discursive analyse of LI in two actual literary contexts: i) first, when it occurs at the beginning of folktales; there, its predicative use is compared to there-sentences, the latter, we argue, being typically speaker-based predications; ii) then, when it occurs in narrative’s descriptions (for instance in crime-scene description); there, LI appears in a context of internal focalization, with the make-belief effect of referring directly to the situation described as if it was perceptible by everyone.In both cases, it appears that LI occurs in contexts where the speaker is pragmatically determined. Its use depends on the need to resort to a "universal" commitment for the predication.